Safety box for camera and electrical devices / Muhammad Hanif Faisal Zaimi Husni - Zaimi Husni, Muhammad Hanif Faisal (2024)
Cameras are one of the most expensive electronic devices and some people use it as a major source of income. Therefore, they must be kept carefully. Most of the new generation camera is not durable and the greatest enemy of a camera are high humidity level. Other than that, because of unreasonable prices even for second-hand cameras and lenses. These items are mostly will be stolen or robbed. With the emergence of the computational era, the old storage box can be improved by using IoT such as Arduino and ESP32. In the current scenario, IoT is considered an active research area for safety features. This study proposed a safety storage box using IoT technology. There will be 2 aims for this study. Which is hardware development that consists of DHT11 sensor to monitor the humidity, a Keypad for password, RFID for faster access, and a buzzer. While the second part is to alert the box owner if the box is getting vibration meaning it moved using mobile approach. Thus, this system will reduce the risk of cameras getting robbed or infected with fungus